'Come this close, but no closer!' Enclave tourism development and social change in Falmouth, Jamaica. Issue 1 (2nd January 2021) - McFarlane-Morris, Shenika
ABSTRACT: The dominant type of tourism development in Jamaica is enclave tourism, characterized by rapid mushrooming of mega all-inclusive facilities – the enclaves. Tourism activities might seem innocuous but on the outside of the enclaves, they often create stark physical and social barriers which exclude and restrict the movements of local populations. The broad objective of this study, which is influenced by the theory of space 'purification' by Sibley (D. (1995). Geographies of exclusion: Society and difference in the west . London and New York: Routledge.), was to critically examine the exclusionary socio-cultural outcomes of tourism in the community of Falmouth, Jamaica, which has the most recent and largest cruise pier in the entire island. The empirical basis of this study centres on qualitative interviews, complemented by data from surveys with local residents. The principal finding of this research is that the Falmouth cruise pier is an 'enclavic' zone of inclusion of tourists but exclusion of the local residents, establishing a new wave of social change. The combination of physical boundaries such as perimeter walls and strong security presence in the town have been used to create and maintain social exclusiveness within the enclaves. Although there is some amount of social interaction between tourists and local residents, the research found that there is a general feeling of marginalization.